Elateriospermum tapos yoghurt as a therapeutic intervention for obesity-associated cognitive impairments and anxiety-like behaviour in a high fat diet maternal obese rat model - Naomi, Ruth; Teoh, Soo Huat; Mahmad Rusli, Rusydatul Nabila; Embong, Hashim; Bahari, Hasnah; Kumar, Jaya (Multidisciplinary Digital Publishing Institute, 2023)
Maternal obesity can be considered an intergenerational cycle and is also an important indicator of cognitive impairments. It is thought that using natural products is the best and safest way to combat maternal obesity and associated complications. Recent studies have shown that Elateriospermum tapos (E. tapos) contains bioactive compounds with anti-obesity effects, and yoghurt is a convenient medium for supplementing obese maternal rats with E. tapos extract. Thus, the aim of this study is to investigate the impact of E. tapos in yoghurt on maternally obese rats’ cognitive function supplemented with a high-fat diet (HFD). In this study, 48 female Sprague-Dawley rats were used. The rats were fed HFD for a period of 16 weeks to induce obesity, after which they were allowed to mate. Upon confirmation of pregnancy, obese rats were given varying doses of E. tapos (5, 50, and 500 mg/kg) in yoghurt until postnatal (PND) day 21. On PND 21, the dams’ body mass index (BMI), Lee index, abdominal circumference, oxidative status, and metabolic profile were measured. The behavioral tests (open field, place, and object recognition) were conducted on PND 21 to access memory. The results show that the 50 and 500 mg/kg E. tapos in yoghurt supplemented groups had similar BMI, Lee index, abdominal circumference, lipid profile, FBG, insulin, FRAP, and GSH levels, as well as a similar recognition index, in comparison with the control group supplemented with saline. In conclusion, the results of this study indicate that the newly formulated E. tapos in yogurt can act as an anti-obesity agent in maternal obesity, alleviate anxiety, and enhance hippocampal-dependent memory.